DKK1 promotes migration and invasion of non–small cell lung cancer via β-catenin signaling pathway - Jing Zhang; Xintong Zhang; Xiaoting Zhao; Mei Jiang; Meng Gu; Ziyu Wang; Wentao Yue (Tumor Biology)
Disregulation of dickkopf-related protein 1 (DKK1) has been reported in a variety of human cancers. However, how DKK1 functions in Non-small cell lung cancer has not been revealed. In the current study, DKK1 was knocked out by the lentivirus-mediated short hairpin RNA interference approach in H1299 and 95C non-small cell lung cancer cell lines. Subsequently, the migration and invasion ability were assessed by wound-healing and transwell assays. In addition, epithelial-mesenchymal transition markers and β-catenin were examined by Western blot analysis. The signaling pathway downstream of DKK1 was characterized using the Wnt signaling pathway inhibitor, IWP2, and glycogen synthase kinase 3 beta inhibitor, LiCl. Immunofluorescence analysis investigated the subcellular localization of β-catenin. The results suggested that knockdown of DKK1 caused reduced migration and invasion ability of H1299 and 95C cells. DKK1 silencing resulted in the downregulation of epithelial-mesenchymal transition-related proteins, such as Snail and zinc finger E-box binding homeobox 1. Besides, DKK1 silencing inhibited β-catenin and promoted the phosphorylation of β-catenin. Mechanism results indicated that the expression of β-catenin was reduced in H1299 or 95C cells after being treated with Wnt signaling inhibitor, IWP2. In addition, the inhibition of β-catenin phosphorylation by glycogen synthase kinase 3 beta inhibitor, LiCl, significantly enhanced the migration and invasion capacities in DKK1-knockdown cell lines. Furthermore, cell immunofluorescence revealed that nuclear β-catenin was reduced when DKK1 was knocked down. Taken together, these findings suggest that DKK1 induces the occurrence of epithelial-mesenchymal transition and promotes migration and invasion in non-small cell lung cancer cells. Mechanically, β-catenin plays a vital role in DKK1-induced non-small cell lung cancer cell migration and invasion, and DKK1 inhibits the phosphorylation of β-catenin, resulting in the increased nuclear localization of β-catenin.